Interfacial properties of hydrides in α-Zr: a theoretical study. (6th September 2017) - Louchez, M-A; Besson, R; Thuinet, L; Legris, A
Abstract: In order to better understand hydride formation in zirconium alloys, heterophase interfaces between α -Zr and γ -ZrH are investigated by means of ab initio atomic-scale simulations of multilayers coupled with continuous elasticity. Our approach allows us to separate out the elastic contribution, leading to basal and prismatic α | γ interface energies around 200 m J ⋅ m − 2 and 750 m J ⋅ m − 2 respectively, i.e. values noticeably higher than previously found for coherent particles such as ζ -Zr2 H. By considering interfacial changes of H contents, the possibility of competing elasticity and chemistry effects for interface stability is analyzed. The effects of the strong anisotropy evident in α | γ interface energies on the important practical issue of preferential habit planes are discussed, allowing us to propose a plausible explanation for the experimental results.